Hybrid cellulose-silica materials from renewable secondary raw resources: An Eco-friendly method - Vasquez-Zacarias, Leticia; Ponce Peña, Patricia; Pérez-López, Tezozomoc; Franco-Urquiza, Edgar A.; Ramírez Galicia, Guillermo; Poisot Vazquez, Martha Emilia (John Wiley & Sons, Inc, 2018)
Hybrid organic–inorganic materials based on cellulose matrix and silica particles are obtained from wastes of the local paper recycling mill and sugarcane mill as renewable secondary raw materials. The performance comparison of these hybrid materials made from secondary raw materials against the materials made from pure, raw sources is discussed. The Fourier transform infrared spectra show that cellulose features prevail even at 43 wt% silica nanoparticles in the hybrid materials. Such a high content of silica originated from sugarcane bagasse ash and hollow glass microspheres contributes to the high thermal stability of the final composites, as seen by thermogravimetric analysis with very low water absorption. This one-step approach of biobased hybrid materials represents an excellent way to produce high-performance materials with high content of inorganic nanoparticles for a wide variety of applications like energy efficient building material completely cement-free.
Keywords: Materiales de construcción sin cemento; Materiales energéticamente eficientes; Materiales híbridos; Materias primas secundarias